The role of the career costs of children for the effect of public child care on fertility and maternal employment - Katrin Huber (Friedrich-Alexander-Universität Erlangen-Nürnberg, Bavarian Graduate Program in Economics (BGPE), 2019)
This paper investigates whether the effects of affordable and easily available public child care on fertility and maternal employment depend on the career costs of children a woman faces. It builds on the idea that these costs vary by occupation and education. In a generalized Diff-in-Diff, I exploit the substantial variation between West German counties concerning intensity and speed of the provision of new child care slots for under-three-year-olds. The combination of county-level data on child care coverage with detailed individual-level information from the German social security records allows me to analyze so far unexplored effect heterogeneities by occupational groups. The results indicate that the average positive effects on fertility and maternal employment are driven by women who face relatively higher career costs of children: women in occupations with a steeper age-earnings profile, women who cannot be easily substituted at work and women with medium and high education level. The findings reveal that policies which reconcile family and work life are indeed more beneficial for women facing higher career costs of having children.
Keywords: J13; J22; 330; Child Care; Fertility; Maternal Employment; Career Costs of Children